2012
DOI: 10.1007/s00520-012-1459-y
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department visits for symptoms experienced by oncology patients: a systematic review

Abstract: Individuals with cancer present to emergency departments with a myriad of symptoms. Over half of emergency department visits resulted in hospital admissions. Few symptoms were defined adequately to compare data across studies, thereby revealing an important gap in cancer symptom reporting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
129
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(162 citation statements)
references
References 37 publications
12
129
0
10
Order By: Relevance
“…A previous study [9] found that pain, respiratory distress, and fever were the most common symptoms in ED visits, and our results were consistent with this fi nding. The high prevalence of lung and gastrointestinal cancers among the study population may explain this; 54.7% of the patients admitted to the ED with shortness of breath were diagnosed with lung cancer.…”
Section: Discussionsupporting
confidence: 93%
“…A previous study [9] found that pain, respiratory distress, and fever were the most common symptoms in ED visits, and our results were consistent with this fi nding. The high prevalence of lung and gastrointestinal cancers among the study population may explain this; 54.7% of the patients admitted to the ED with shortness of breath were diagnosed with lung cancer.…”
Section: Discussionsupporting
confidence: 93%
“…2 In systematic review of 18 studies examining emergency department (ED) visits among oncology patients, more than half of ED visits resulted in hospital admissions. 9 However, reports of toxicities experienced by oncology patients were inadequate to synthesize data across studies, highlighting the need for consistent use of patient-reported toxicity measures. 9 Furthermore, regular assessment of toxicities among oncology patients can predict ED visits.…”
Section: Introductionmentioning
confidence: 99%
“…9 However, reports of toxicities experienced by oncology patients were inadequate to synthesize data across studies, highlighting the need for consistent use of patient-reported toxicity measures. 9 Furthermore, regular assessment of toxicities among oncology patients can predict ED visits. In a cohort study of more than 45,000 oncology patients in Canada, the patient-reported Edmonton Symptom Assessment Scale was used to predict subsequent ED visits within 7 days of assessment.…”
Section: Introductionmentioning
confidence: 99%
“…7 Pain is the most frequent symptom to prompt unscheduled medical care in oncology patients. [8][9][10] Cancer charities in the UK have raised concerns about pain management in the OOH period. 11,12 OOH primary care in the UK is accessed via centralised telephone systems, and provided by healthcare practitioners from a variety of professional backgrounds.…”
Section: Introductionmentioning
confidence: 99%